ECOLOGICAL RISK ASSESSMENT OF LIQUID WASTE ON SURFACE WATER IN WARRI SOUTH-WEST, L.G.A. DELTA STATE - Eyankware, Ruth O. Ulakpa; Uchenna, Elizabeth U.; Ulakpa, Wisdom Chukwuemeke (FUDMA Journal of Sciences, 2025)
The Niger Delta, a key center for Nigeria's oil production, has undergone severe ecological damage over decades from oil extraction, effluent releases, and ineffective waste handling. In Warri South-West LGA, Delta State, the Escravos estuary, essential for fisheries, navigation, and rich biodiversity suffers heavy pollution from wastes, elevating heavy metal concentrations and compromising water integrity. Using geo-chemical indices, this study evaluates the ecological risk of liquid waste on surface water in the Escravos estuary.  The result revealed that pH ranged from 5.90 to 6.80, temperatures were steady between 27.0 and 27.5°C, and the turbidity was high, over the standard limits, owing to pollution from anthropogenic activities. Threatening health, the levels of heavy metals Cd (0.062-0.211 mg/L), Hg (0.027-0.081 mg/L), Cr (0.011-0.410 mg/L), and Pb (0.017-0.040 mg/L) were all above the standards set by the WHO. The geo-chemical indices (CF, MPI, PLI, HEI, mCd, PIS, and WQI) showed moderate to severe pollution; the most polluted areas were ES01/02 (WQI: 42,206) and ES02/01 (HEI: 44.88), both of which were caused by industrial effluents. With WQI of 15,272, ES03/01 (x) was the cleanest sample, though other samples had high concentrations of Cd and Pb. Among the public health and ecological concerns raised by the results are the potential for bioaccumulation in aquatic organisms and the long-term impacts of exposure, such as neurotoxicity and kidney impairment. This finding suggests that to protect water resources and reduce pollution in the Niger Delta area, immediate remediation and stronger regulatory interventions are needed.
Keywords: Ecological Risk Assessment; Liquid Waste; Surface Water; Warri South-West LGA; Delta State